Increasing Self-Medication Knowledge of Administrators in the Child Social Welfare Institution - Muslim, Zamharira; Susilo, Avrilya Iqoranny; Pudiarifanti, Nadia; Meinisasti, Resva; Krisyanella, Krisyanella; Khasanah, Heti Rais; Irnameria, Dira (Universitas Padjadjaran, 2023)
Child Welfare Institution (CWI) managers often provide self-treatment or self-medication when foster children experience mild symptoms of illness. In its implementation, self-medication often results in inaccuracies. For this reason, it is necessary to increase the self-medication knowledge capacity of CWI managers in Bengkulu City. The aim of this activity is to increase knowledge about self-medication by CWI managers. This activity provides knowledge about how to manage medicines properly and correctly. The training was given using the Active Human Learning Method which was attended by 30 people. Based on the pretest results, the average score was 5.73, while the posttest results showed an increase in the average score to 7.27 and was tested by an independent t-test (p=0.000). Increasing this knowledge is important in supporting rational drug use programs. Keywords: Child Welfare Institutions, knowledge, self-medication.